"That's frustrating": Perceptions of ankle foot orthosis provision, use, and needs among people with cerebral palsy and caregivers. Issue 2 (April 2023) - Zaino, Nicole L.; Yamagami, Momona; Gaebler-Spira, Deborah J; Steele, Katherine M.; Bjornson, Kristie F.; Feldner, Heather A.
Abstract : Background: Cerebral palsy (CP) affects roughly 3 per 1000 births in the United States and is the most common pediatric developmental motor disability. Ankle foot orthoses (AFOs) are commonly prescribed to provide support and improve function for individuals with CP. Objectives: The study objective was to evaluate the lived experiences of individuals with CP and their caregivers regarding AFO access, use, and priorities. We examined experiences around the perceived purpose of AFOs, provision process, current barriers to use, and ideas for future AFO design. Study design: Secondary qualitative data analysis. Methods: Secondary data analysis was performed on semistructured focus groups that included 68 individuals with CP and 74 caregivers. Of the focus group participants, 66 mentioned AFOs (16 individuals with CP and 50 caregivers). Deidentified transcripts were analyzed using inductive coding, and the codes were consolidated into themes. Results: Four themes emerged: 1) AFO provision is a confusing and lengthy process, 2) participants want more information during AFO provision, 3) AFOs are uncomfortable and difficult to use, and 4) AFOs can benefit mobility and independence. Caregivers and individuals with CP recommended ideas such as 3D printing orthoses and education for caregivers on design choices to improve AFO design and provision. Conclusions: Individuals with CP and their caregivers found the AFO provision process frustrating but highlight that AFOs support mobility and participation. Further opportunities exist to support function and participation of people with CP by streamlining AFO provision processes, creating educational materials, and improving AFO design for comfort and ease of use.